(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with psychological factors of the formation of foreign students’ cross-cultural competence in the process of learning Ukrainian, to which belong such ones as interest to the national character, social and cultural differences, as well as educational, professional and social motives.